NAD+ Degrading Enzymes, Evidence for Roles During Infection - Tan, Arnold; Doig, Craig L. (Frontiers in Molecular Biosciences, 2021)
Declines in cellular Nicotinamide Adenine Dinucleotide (NAD+) contribute to metabolic dysfunction, increase susceptibility to disease, and occur as a result of pathogenic infection. The enzymatic cleavage of NAD+, transfers ADP-ribose (ADPr) to substrate proteins generating Mono-ADP-ribosylation (MAR), Poly-ADP-ribosylation (PAR) or O-acetyl-ADP-ribose (OAADPr). These important post-translational modifications have roles in both immune response activation and the advancement of infection. In particular, emergent data show viral infection stimulates activation of poly(ADP-ribosyl) polymerase (PARP) mediated NAD+ depletion and stimulates hydrolysis of existing ADP-ribosylation modifications. These studies are important for us to better understand the value of NAD+ maintenance upon the biology of infection. This review focusses specifically upon the NAD+ utilising enzymes, it discusses existing knowledge surrounding their roles in infection, their NAD+ depletion capability and their influence within pathogenic infection.